2012
DOI: 10.3233/wor-2012-1297
|View full text |Cite
|
Sign up to set email alerts
|

Transcultural healthcare immersion: A unique interprofessional experience poised to influence collaborative practice in cultural settings

Abstract: in Cultural Settings [1] represents a guiding framework predicated on a conceptual "brick and mortar" process for building cultural proficiency among individuals and within teams. It encompasses social, clinical and behavioral components (brick) and personal desire, cultural humility and values (mortar). The "bounty" aspect of the model is achieved by way of successful student learning outcomes, positive interprofessional and community-based collaborations, and finally, and to be measured over time, favorable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 2 publications
1
11
0
Order By: Relevance
“…Interactions between the professional faculty members were modeled, yet perhaps intentional debriefing outlining the professional interactions would have created greater impact. The overall findings of our study are corroborated by published studies examining impact on health profession students in service learning (DeBonis, 2016) interprofessional service learning (De Los Santos, McFarlin, & Martin, 2014); and improving confidence in different cultures (Dupre, 2007;Kohlbry, 2016;Morton, 2011).…”
Section: Discussionsupporting
confidence: 86%
“…Interactions between the professional faculty members were modeled, yet perhaps intentional debriefing outlining the professional interactions would have created greater impact. The overall findings of our study are corroborated by published studies examining impact on health profession students in service learning (DeBonis, 2016) interprofessional service learning (De Los Santos, McFarlin, & Martin, 2014); and improving confidence in different cultures (Dupre, 2007;Kohlbry, 2016;Morton, 2011).…”
Section: Discussionsupporting
confidence: 86%
“…This attribute is defined as a critical process of reflecting on one’s thoughts, feelings, and actions. Terms used that fall under this heading included self-reflection, self-critique, thinking critically about one’s self, self-evaluation and critique, self-reflection and discovery, self-questioning and critique, reflection, self-reflective process, knowledge acquisition and reflective practice, reflective openness, and introspection (American Association of Diabetes Educators, 2012; Chang et al, 2012; Clark et al, 2011; Coulehan, 2010; Fahey et al, 2013; Foster, 2009; Hammell, 2013; Hilliard, 2011; Isaacson, 2014; Ma et al, 2014; Miller, 2009; Morton, 2012; Nazar et al, 2014; Reynoso-Vallejo, 2009; Ross, 2010; Schuessler, Wilder, & Byrd, 2012; Vogt, 2011; Yeager & Bauer-Wu, 2013). The self-reflection and critique was described as a journey or endless process of continual reflection and refinement.…”
Section: Resultsmentioning
confidence: 99%
“…Studies addressing self-perceptions of professional skills are difficult to compare because of variation in the way professional skills are defined. Many studies have addressed cultural awareness and understanding as a professional skill, and it is often mentioned as a skill that tends to improve with a community-based experience (e.g., Black & Wells, 2007;Doll, 2011;Gitlow, 2011;Meyers, 2009;Morton, 2012;Perrin & Wittman, 2001;Scott, 2004;Velde & Wittman, 2001;Velde, Wittman, & Mott, 2007). Black and Wells (2007) indicated that every clinical interaction involves multiple cultures and cited Fitzgerald (1992), who observed that in clinical interaction at least three cultures are involved: the personal culture of the provider, the personal culture of the client, and the culture of the primary medical system.…”
Section: Professional Skillsmentioning
confidence: 99%
“…Moreover, students in CF learn how to propose, develop, and implement occupational programs at community sites (Flecky, 2011;Scott, 2004). CF also has been found to provide students with opportunities to explore different cultures and overcome stereotypical thinking concerning minority populations (Black & Wells, 2007;Bourke & Hudson, 2005;Doll, 2011;Forwell, Whiteford, & Dyck, 1997;Gitlow, 2011;MacRae, 2012;Moffett & Garbarini, 2004;Morton, 2012;Perrin & Wittman, 2001;Velde & Wittman, 2001).…”
mentioning
confidence: 99%